2018
DOI: 10.1097/md.0000000000011891
|View full text |Cite
|
Sign up to set email alerts
|

Association of gestational diabetes mellitus and abnormal vaginal flora with adverse pregnancy outcomes

Abstract: Gestational diabetes mellitus (GDM) is associated with adverse perinatal outcomes. This study aimed to examine the association between GDM and abnormal vaginal flora, and the association between abnormal vaginal flora and adverse pregnancy outcomes.This was a prospective study of pregnant women who visited Xuanwu Hospital of the Capital Medical University (Beijing, China) between February and October 2015. All women were screened for GDM according to the International Association of the Diabetes and Pregnancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 49 publications
8
61
0
1
Order By: Relevance
“…This finding was consistent with a study done previously in Iran where they found no association between vaginal Candida colonization and low birth weight [39]. The current study has also shown that Candida species cause gestational complications which is also in agreement with a previous study done in China [40] Among the different studied variables which may be affected by Candida, such as gestational complications, gestational diabetes, vaginal discharge, induced labor and recurrent UTI, the present study confirmed that the presence of C.albicans was significantly associated with women with gestational diabetes and both C.krusei and C.glabrata on womenwith gestational complications.…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with a study done previously in Iran where they found no association between vaginal Candida colonization and low birth weight [39]. The current study has also shown that Candida species cause gestational complications which is also in agreement with a previous study done in China [40] Among the different studied variables which may be affected by Candida, such as gestational complications, gestational diabetes, vaginal discharge, induced labor and recurrent UTI, the present study confirmed that the presence of C.albicans was significantly associated with women with gestational diabetes and both C.krusei and C.glabrata on womenwith gestational complications.…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with a study done previously in Iran where they found no association between vaginal Candida colonization and low birth weight [39]. The current study has also shown that Candida species cause gestational complications which is also in agreement with a previous study done in China [40] Among the different studied variables which may be affected by Candida, such as gestational complications, gestational diabetes, vaginal discharge, induced labor and recurrent UTI, the present study confirmed that the presence of C. albicans was significantly associated with women with gestational diabetes and both C. krusei and C. glabrata on women with gestational complications.…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with a study done previously at Iran where they found no association between vaginal candida colonization and low birth weight [47]. The current study has also shown that candida species cause gestational complication and vaginal discharge which is an agreement with a previous study done in China [48], therefore screening and treatment are essential in pregnant women.…”
Section: Discussionsupporting
confidence: 93%